The societal burden associated with adolescent idiopathic scoliosis: a cross-sectional burden-of-disease study - Thomáy-Claire Ayala Hoelen; Silvia M. A. A. Evers; Jacobus J. Arts; Paul C. Willems; Ghislaine A. P. G. van Mastrigt (BMC Public Health)
Abstract Background In the general population the prevalence of adolescent idiopathic scoliosis (AIS) is 2–3%. There is growing awareness of how AIS affects the quality of life of patients. However, the extent of the societal burden AIS poses remains poorly understood. Therefore, this study aimed to determine the societal burden of AIS. Methods A cross-sectional burden of disease study was conducted using a bottom-up, prevalence-based approach. Patients with AIS or guardians of a child diagnosed with AIS residing in the Netherlands were eligible for inclusion. The survey was distributed between June - December 2022 and was completed once by each participant. Costs were assessed using the institute for Medical Technology Assessment - Medical Consumption and Productivity Cost Questionnaires. The health-related quality of life (HRQoL) was assessed using the EuroQol 5D-5L/EuroQol 5D Youth and the Scoliosis Research Society-22 revised questionnaires. Costs and HRQoL were identified, measured, and valued. Results Participants (n = 229) were predominantly female (92%), on average 35 years old, and were employed (65%). The societal cost for a patient with AIS in the Netherlands was €12,275 per year. The largest costs were estimated for the healthcare and productivity losses. The mean utility score for adults was 0.7 (SD 0.20). Severe pain was experienced by 10% of the adult participants and 44% reported to experience moderate pain/discomfort. Statistically significant differences between different age groups were present for the sector costs and HRQoL. Conclusions AIS negatively impacts societal costs and the HRQoL. Reducing the burden that is posed on the productivity sector by AIS and further improving the HRQoL for AIS patients is needed.